Aplikasi Sistim Perlindungan Katodik Pada Kapal Tenggelam Sebagai Benda Cagar Budaya - (Program Diploma III Teknik Perkapalan Fakultas Teknik Universitas Diponegoro), Eko Julianto S., Sul (Teknis, 2015)
In Indonesia, a lot of cultural heritage made of metal found under water in the form of a shipwreck, cannons, anchors and even submarines. Metal is the material that is prone to damage due to corrosion. Metals are submerged in sea water will corrosion rate at high speed. Cathodic protection system is a way of preventing corrosion with an efficient control of the redox potential and not destructive. Sacrificial anode round method is a cathodic protection system is more practical applied to cultural heritage made of metal found under water. The application field is selected on the steel ship that sank in 1960 in the waters of Karimunjawa, Jepara. The metal used as a sacrificial anode is zinc alloy. Measurement data is resistance, potential and electric current generated in the sacrificial anode zinc alloy and steel ship with outboard boats carried on the location of the shipwreck. Measurements were made with a multimeter, voltmeter and ampere meter. From the calculation, it can be concluded that the cathodic protection system to prevent corrosion of the steel ship that sank as objects of cultural heritage with an area of 1436.61 m2 within 7 (seven) years requires zinc alloy sacrificial anodes as heavy as 485 kg.Keywords: shipwreck, cathodic protection, cultural heritage